Reproductive conflict resolution in cooperative breeders. (29th August 2019) - Cram, Dominic L; Jungwirth, Arne; Spence-Jones, Helen; Clutton-Brock, Tim
Abstract: Female infanticide is common in animal societies where groups comprise multiple co-breeding females. To reduce the risk that their offspring are killed, mothers can synchronize breeding and pool offspring, making it hard for females to avoid killing their own young. However, female reproductive conflict does not invariably result in reproductive synchrony, and we lack a general hypothesis explaining the variation in conflict resolution strategies seen across species. Here, we investigate the fitness consequences of birth timing relative to other females and the prevalence of birth synchrony in cooperatively breeding Kalahari meerkats ( Suricata suricatta ). We show that, although there would be substantial benefits to females in synchronizing births and reducing their risk of infanticide, birth synchrony is rare. Since precise breeding synchrony has evolved in a related species with similar infanticidal female reproductive conflict, its absence in meerkats requires an evolutionary explanation. We therefore explore the costs and benefits of synchronizing breeding in two theoretical models, each of which contrasts synchrony with an alternative reproductive strategy: (i) breeding opportunistically and accepting fitness losses to infanticide or (ii) suppressing the reproduction of others to prevent infanticide. Our models show that the costs of synchrony constrain its development if subordinates breed infrequently, and that selection instead favors the suppression of subordinate reproduction by the dominant and opportunistic reproduction by subordinates. Together, our results suggest that the resolution of reproductive conflict in animal societies is shaped by differential breeding propensities among female group members, leading to divergent conflict resolution strategies even in closely related species. Abstract : In animal societies, the extent to which females breed in synchrony depends on the females that breed least often. In some social animals, breeding females kill young that would compete with their own. Females therefore breed synchronously, to confuse young identity and prevent infanticide. We show that, by contrast, meerkats breed out-of-sync. This is because younger females rarely breed, so the alpha-female opts to prevent them breeding altogether, rather than synchronizing with them.